ASPEK-ASPEK DALAM IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2014 TENTANG KESEHATAN IBU, BAYI BARU LAHIR, BAYI, DAN ANAK BALITA PADA DESA CEMPAKA KECAMATAN AMUNTAI SELATAN KABUPATEN HULU SUNGAI UTARA - norsanti norsanti; fatimah ayu ningsih (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
The vision of the health development in the future is "Indonesia sehat (Healthy Indonesia)". Problems related to the implementation of the local law of KIBBLA in the village of Cempaka South Amuntai subdistrict is that many cases of labor process is not performed in health facilities, poor mother and infant health. One of the efforts of the Local Government regency of Hulu Sungai Utara to decrease maternal and infant mortality cases and to ensure the health of mothers, infants and children under five is to make a policy through the regulation regency of Hulu Sungai Utara number 3 in 2014 that regulate the health of mothers, newborns, Infants and toddlers (KIBBLA). Problems related to the implementation of the local law of KIBBLA in the village of Cempaka South Amuntai subdistrict is that many cases of labor process is not performed in health facilities, poor mother and infant health. Result of the research showed that implementation of Perda KIBBLA in the village of Cempaka in some aspects is already good, seen from communication, staff, and commitment. However, from several points also need improvements in order to support the implementation of Perda KIBBLA, such as polindes / puskesdes and also SOPs (Standard Operating Procedure).